“Seems I’m Not Alone at Being Alone:” Potential Factors Contributing to Drinking Games in the College Setting - Kilmer, Jason R. (Am J Drug Alcohol Abuse, 2014)
Alcohol use among college students is prevalent and sometimes takes the form of drinking games, in which players are required to drink in accordance with a set of pre-defined rules. Drinking games are typically associated with elevated alcohol consumption and risk to the individual. This perspective piece considers the potential role of social anxiety in motivating participation in drinking games, perceived norms surrounding drinking games (including ways they are portrayed and discussed in popular media), and the role of competitiveness. Implications for skills training-based prevention and intervention efforts are discussed.